AI-Enhanced RSM Optimization of Green-Treated Spent Coffee Grounds for Superior Chromium (VI) Removal - Nguyen, Tuan Anh; Nguyen, Xuan Huy; Nguyen, Thi Thu Phương (Trends in Sciences, 2026)
In this study, spent coffee grounds (SCG) were chemically activated with Ca(OH)₂ to develop a sustainable adsorbent for Cr(VI) removal from aqueous solutions. Structural analyses (SEM/EDX, FTIR, XRD, and XPS) confirmed that Ca(OH)₂ pretreatment significantly enhanced surface porosity, exposed additional oxygen-containing functional groups (–OH, –COOH), and introduced Ca–O active sites, thereby improving adsorption performance. The adsorption efficiency was strongly influenced by solution pH. Although the highest removal efficiency was observed under strongly acidic conditions (pH ≈ 2), extremely low pH values are not desirable for practical water treatment due to excessive acid consumption and potential corrosion. Therefore, an operational pH range of 4.5 - 5.0 was selected as the optimal condition to balance adsorption performance and practical applicability. Under these conditions (initial concentration ≈ 50 mg L⁻¹, dosage 1.0 g/100 mL, contact time 180 min, temperature 313 K), the maximum adsorption capacity reached 21 - 22 mg g⁻¹ with a removal efficiency of 88% - 90%, compared with only 12 - 14 mg g⁻¹ for untreated SCG. Kinetic analysis demonstrated that the pseudo-second-order (PSO) model best described the adsorption process (R² ≥ 0.993), while isotherm studies revealed good agreement with both Freundlich (R² = 0.984 - 0.992) and Langmuir (R² = 0.980 - 0.993) models, suggesting heterogeneous adsorption with partial monolayer characteristics. Thermodynamic analysis indicated an endothermic adsorption process (ΔH° > 0), with qₘₐₓ increasing from 20.83 mg g⁻¹ (298 K) to 23.45 mg g⁻¹ (328 K). High-resolution XPS spectra confirmed that the adsorbed chromium existed in mixed oxidation states, with partial reduction from Cr(VI) to Cr(III), particularly in SCG4 (2.5 wt% Ca(OH)₂), where the Cr(III)/Cr(total) ratio was highest. Reusability tests showed that after ten adsorption–desorption cycles, the removal efficiency remained at approximately 44%, demonstrating the material’s stability and regeneration potential. These results indicate that Ca(OH)₂-modified SCG is a low-cost, eco-friendly, and effective adsorbent for chromium-contaminated water treatment, combining efficient Cr(VI) removal, partial detoxification, and good recyclability. HIGHLIGHTS Sustainable Ca(OH)₂ activation significantly improved SCG surface chemistry and adsorption performance. High Cr(VI) removal efficiency (up to 90%) achieved at practical pH (4.5–5.0). Hybrid RSM–AI modeling revealed nonlinear structure–performance relationships with superior prediction accuracy. Combined adsorption–reduction mechanism enabled detoxification of Cr(VI). Waste-derived adsorbent offers a scalable and eco-friendly solution for water treatment. GRAPHICAL ABSTRACT